Current status of groundwater arsenic and its impacts on health and mitigation measures in the Terai basin of Nepal: An overview - Yadav I.C.; Dhuldhaj U.P.; Mohan D.; Singh S. (My University, 2025)
Nepal is located in the vicinity of Himalayas. Nearly 47% (11 million) of the total Nepalese population lives on the flat lands located in the southern part of the country, the Terai region. The majority (90%) of people living in the Terai region of Nepal depends on groundwater as their primary source of potable water. Out of 24 674 tested wells in the Nawalparasi district approximately 7896 wells (32%) had As concentrations greater than 10 μg·L-1 (safe-water limit set by WHO). In addition, 3676 wells (14.9%) had As concentrations greater than 50 μg·L-1 (standard permissible limit proposed by Nepal). However, at present, none of the wells in the Terai districts of Nepal are free from As. Based on sedimentaquifer studies, the Siwalik Hills and the higher Himalayas are assumed to be the possible sources of As in the Terai region. Leaching of As from natural rocks has been the main source of groundwater contamination in Nepal. However, little is known about the mechanism of As release in the Terai groundwater. High levels of As contamination in the drinking water poses a serious risk to the health of resident living in the Terai plain regions. In the region, 23% (2.53 million, based on WHO guideline of μg·L -1) and 5% (0.5 million, Nepal's standard of >50 μg·L-1) of population are at the risk of As exposure. Chronic exposure to As imparts characteristic skin manifestations (pigment change), melanosis and keratosis. The prevalence of arsenicosis was found to be 3.6%, 0.9%, and 0.7% in Nawalparasi, Rupandehi, and Kapilavastu districts, respectively. Arsenicosis is most prevalent among the male population, especially those in their late 50s. The most promising approach for the removal of As to acceptable levels include the use of Gagri filters and iron-assisted bio-sand filters. Here, we review the current status of groundwater arsenic and its impacts on health and mitigation measures in the Terai region of Nepal.